The Impact of Fuelwood Moisture Content on the Emission of Gaseous and Particulate Pollutants from a Wood Stove. Issue 1 (2nd January 2023) - Price-Allison, Andrew; Mason, Patrick E; Jones, Jenny M.; Barimah, Eric K.; Jose, Gin; Brown, Aaron E.; Ross, Andrew B; Williams, Alan
ABSTRACT: The amount of moisture in wood fuel has a significant influence on the emissions of particulate matter (PM) and gaseous pollutants when burned in small-scale domestic appliances. Previous studies have shown that higher moisture content generally produces higher particulate emissions factors. As well as quantity of material emitted, it is also important to understand the effects of moisture on particle qualities including size, composition and morphology – since these can influence the human-toxicity and environmental impacts of the particles. In this study, emissions were quantified and the particulate qualities were also examined using chemical, optical and thermogravimetric analysis as well as size-graded sampling. By comparing the results from the use of batches of beech wood fuel with differing moisture content, it was shown that there are consistent and significant differences in both the quantity and qualities of the resulting emissions when burned under the same conditions. This has important consequences for emission inventories which currently only assume an emission factor from a proscribed combustion situation